Electrical Currents from Diffusion Equation and Electrodynamics at Targeted Drug Delivery Strategies - Nieto-Chaupis, Huber (2021)
This paper presents a theoretical approach of a prospective scheme inside Nanomedicine known as Targeted Drug Delivery (TDD) based entirely on Classical Electrodynamics. Under the assumption that nanoparticles can be electrically charged because their ionic composition, any specific task for delivering a certain amount of biochemical compounds might to involve additional electrical interactions that would limit the efficiency of the action of delivery. In this manner, the apparition of repulsive electrical forces would be translated as the fail of the task. Therefore, nanoparticles would have to be engineered with a minimal response to electrical forces, so that one expects that nano cargo accomplishes its main role at Nanomedicine.